Postmodernity, public management and information and communication technologies in the public administration of Ecuador - Barragán Martínez, Xavier (2022)
During the COVID-19 health emergency in Ecuador, new public administration practices were introduced to minimize bureaucratic problems and improve traditional public management. The purpose of this article is —from a postmodern perspective— to analyze the new paradigm of public administration, the new Information and Communication Technologies (ICT) and the innovations in Public Management of Ecuador. Based on an analytical, descriptive, and qualitative methodology, whose primary source was a survey of 29 public officials belonging to four (out of five) State functions. The results show that technological innovations can be replicated and applied easily in other public entities with needs of solutions in monitoring and control of resources, access control, document, and accounting management.